Transgenic mosquito: from paper to reality - Oliveira, Soraia de Lima; Carvalho, Danilo Oliveira; Capurro, Margareth Lara (Revista da Biologia, 2018)
Vector-borne diseases are currently the worst challenge of public health in Brazil and worldwide, being the current control measures inefficient. Innovations concerning vector control point to a new perspective to handling with gene engineering, as they may interfere with disease transmission, preventing the pathogen to complete its cycle in the vector, ie, reducing mosquito population. We present some of the mean genetic tools available, SIT and RIDL for example. We discuss how these tools work, some risks and benefits